Premchand and Mulk Raj Anand; Two Novelists with Same Vision: A Comparative Study of Premchand and Mulk Raj Anand's Reflection of Social Realism in Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper, while making a modest endeavor to work out a comparison between the two acclaimed Indian journalists and social democracy, Premchand and Mulk Raj Anand, aims at penetrating the grounds and parameters of their delineation of the reality. Premchand and Anand have commanded gigantic regard in the literary realms and have been estimated as leading figures in their particular fields by faultfinders and scholars. The present thesis is a humble and novel attempt to make sense of how these two stalwarts have reflected social realism in their novels as also to make a thorough, comparative and critical appraisal opposite their art and ideas. It is trusted that it will introduce the two great authors in another viewpoint, profiting scholars of both English and Hindi literature. Since the domain of their novels is extremely vast, the investigation deals with a chose bit of it. So far as crafted by Premchand are concerned, a special reference has been made to his novels Sevasadan (1918), Kayakalpa (1926), Gabon (1931) and Godan (1936). The novels of Mulk Raj Anand Coolie (1936), two leaves and a Bud (1937), The Road (1961) and The Bubble (1984) have been worked out keeping in view the destinations of the examination.